Pengaruh Ketinggian Tempat Tumbuh Terhadap Kandungan Fitokimia dan Antioksidan Ekstrak Akar Sawi Langit (Vernonia cinerea L.) - Sri Lestari; Riska Desi Aryani; Dian Palupi (Biotropic : The Journal of Tropical Biology, 2021)
This study aims to determine the effect of altitude on the phytochemical and antioxidant content of sawi langit (Vernonia cinerea L.) root. Sawi langit is a herbaceous plant that has potential as a medicinal plant. This plant can thrive in the tropics. In this study, sawi langit were taken from three altitudes, namely <400 masl, 401-800 masl and >801 masl in the Banyumas, central Java. The sample used was sawi langit root which was extracted using 3 types of solvents (methanol, ethyl acetate and n-hexan). Phytochemical tests showed positive results of the content of flavonoid, alkaloids, tannins, terpenoids and saponins compounds in the extract of sawi langit root from the three altitude with differences effectiveness of each solvent. At an altitude of <400 masl and extraction using methanol resulted strong antioxidant activity with an IC50 value 78.56 ± 3.2  μg/ml compared to an altitude of 401-800 masl and >801 masl